Motivation towards the practice of physical activities in assistants of the gerontological center "Las Piñas" of the Milagro Canton/Motivación hacia la práctica de actividades físicas en asistentes del centro gerontológico las Piñas del Cantón Milagro - Verónica Janeth Vaca Catute; Fernando Alfonso Cedeño Alejandro (Podium, 2022)
Introduction: Motivation allows the individual to stay in a given action, enables the effectiveness of pertinent processes for the achievement of a specific or general objective, which in the case of physical activity is related to its systematicity and, therefore, the maintenance of a better lifestyle. Objective: The research focused on diagnosing the motivation towards the practice of physical activities in Assistants of the "Las Piñas" Gerontological Center of the Milagro Canton. Materials and methods: The methodology used responds to a descriptive-explanatory research, of a qualitative nature. With a type of non-probabilistic sampling, 60 older adults are studied as a participating population, classified by gender. An adapted research instrument was used, applying the Rossemberg test as a basis and a valid survey for the measurement of the two variables. Results: The results of the research determined that there is a high percentage of adults who are sedentary, in relation to gender it was found that women have a higher rate of inactivity than men, without significant differences (p=0.982). Another response found is that many older adults find the perception of not being able to keep up with others, illnesses, fear of injury, among others, as limitations to physical activity, being variables of consideration in the prospective design of a strategy playful to improve the quality of life of the samples under study. Conclusions: As part of the conclusions, it is suggested that changes be made in the lifestyle of the older adults studied, the main thing is the motivation that can be instilled in them from home and from families.